Other-oriented perfectionism in adolescents: differences in internalizing and externalizing problems, as well as in prosocial behavior - Fuster, Andrea; Pérez-Marco, María; Vicent, María (Frontiers in Psychology, 2025)
IntroductionThe scientific evidence has demonstrated that other-oriented perfectionism is negatively related to internalizing and externalizing problems only in adults. However, there is a disagreement about how this perfectionistic dimension is associated with prosocial behavior in adults and adolescents. Moreover, there is a lack of knowledge about how other-oriented perfectionism is associated with those variables in youth population. For this reason, the aims of this study were to: (1) examine differences between students with high and low scores on internalizing and externalizing problems, and prosocial behavior based on other-oriented perfectionism; and (2) determine the likelihood of exhibiting high levels of these indexes based on perfectionism scores.Method681 students aged 12 to 16 (M = 14.14, SD = 1.31), completed the Other-Oriented Perfectionism Subscale-Junior Form and the Strengths & Difficulties Questionnaire.ResultsThe three indexes (i.e., internalizing problems, externalizing problems, and prosocial behavior) were calculated as the mean of the subscales that composed each index. After obtaining the total scores of internalizing problems, externalizing problems, and prosocial behavior, the scores of each were dichotomized into high and low scores. Student's t-test reported significant differences between students with high and low scores on the three indexes based on the other-oriented perfectionism dimension. Furthermore, the logistic regression analysis reported that the probability of exhibiting a high level of internalizing and externalizing problems increases for each point increase in other-oriented perfectionism. Contrarily, the likelihood of displaying a high index of prosocial behavior decreases for each point increase in this perfectionistic dimension.DiscussionThe results suggest the maladaptive role of other-oriented perfectionism, underscoring the need for further research on how this perfectionistic dimension impacts the educational environment.